Factors influencing the use of postoperative bilevel positive airway pressure (BiPAP) in patients undergoing adult cardiac surgery: A retrospective cohort study. Issue 6 (3rd October 2022) - Ahmed, Syed S.; Yousuf, Muhammad S.; Samad, Khalid; Ullah, Hameed; Siddiqui, Khalid M.
Abstract: BAckground and Aims: Respiratory complications are one of the biggest challenges following cardiac surgery, which can lead to hypoxia and acute respiratory failure (ARF). The aim of this study to identify the factors led to BiPAP application for postoperative respiratory complications and its effectiveness as the main outcome measures after cardiac surgery. Methods: It was a retrospective cohort study with consecutive sampling technique. A total of 335 postcardiac surgery patients medical record was reviewed who were underwent for surgery from November 1, 2018 to November 30, 2019. 265 patients were finalized for the recruitment, five patients were excluded before the final analysis. Data of 260 patients were analyzed for compiling of results. Results: The mean age was 59 years. 196 (75.4%) patients were males and females were 64 (24.6%). Mean weight was 72 kg and mean body mass index (BMI) 26.67 kg/m 2 . BiPAP application was in 38 (14.6%) patients and significantly high in with high BMI, ( p  < 0.05). There are significant associations of BiPAP application patients with COPD ( p  < 0.05). Patients with positive fluid balance, cardiac dysfunction, and required inotropic support were significantly associated with BiPAP need ( p  < 0.05), respectively. Conclusion: BiPAP is effective to treat ARF and other respiratory complications after adult cardiac surgeries. High BMI, atelectasis, and pneumonia are also the independent factors causing ARF. BiPAP can be a successful tool for preventing the adverse effects of postoperative pulmonary complications after cardiac surgery.